O jogo dos gêneros e o gênero do jogo: o caso do voleibol - Oliveira, Leonardo Erivelto Soares de (Universidade Federal de São Carlos, 2010)
Through an ethnography based on my own sports biography, I demonstrate the coexistence of powerful conceptions about volleyball that make it appear as “female sport”, “women's sport” and/or “sport of fagots”, among other variants, and the volleyball players’ conceptions about the sport they practice. The central argument of this research is that such conceptions are supported by a set of factors: the contrast between soccer and volleyball, respectively first and second sports in national preference, coupled with a certain view on body techniques in general and on the techniques of volleyball in particular, which merge with a peculiar context marked by the large presence of women, "gays" and certain uses of the body, at least in the amateur circuit.
The game of the genders and the gender of the game: the case of volleyball
Keywords: Antropologia dos esportes; Voleibol; Futebol; Gênero; Técnicas corporais; Anthropology of sports; Volleyball; Soccer; Gender; Body techniques; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA